The exposition of generators and electrodes belonging to the pacemaker in pacemaker dependent patients: A new management method - Kapukaya, Rana; Karakol, Percin (Annals of Medical Research, 2021)
Aim: In patients with pacemakers, their exposure is often mortal, as there are already patients whose general condition is impaired. In our study, by focusing on our different recommendations and exposition formation mechanisms in case of a need for re-operation when exposition and necrosis in the skin flap is observed in 8 patients who were fitted with cardiac pacemakers due to being dependent on batteries, we shared what could be done in order to prevent it from happening from the beginning.Materials and Methods: Exposed batteries and connections of 8 patients who had admitted due to pacemaker exposition between January 2015- March 2017 were carefully dissected and removed. The generator and leads were replaced with new ones and carried by opening a new subpectoral pocket on the opposite side by creating a subcutaneaus tunnel on the sternum. The area on the left side where the skin flap with development of necrosis was located was debrided. It was reconstructed with fasciocutaneous flap. Results: All patients were successfully treated. No complications were observed during the follow-up period.Conclusion: In cases where large necrosis develops at the pacemaker exposition and on the skin island, it is an effective treatment method to replace the battery with all its connections due to the biofilm layer formed on it with extracardiac lead and to place it in a new subpectoral pocket opened on the other side by tunnelizing. Since exposition is seen mostly in patients with thin subcutaneous fat tissue, pressure can be mechanically prevented by also involving muscle from the beginning or by placing in deeper tissue. Technically, the greatest advantage of the method that we recommend is that it can be done under local anesthesia. Keywords: Exposition; pacemaker; reconstruction